2005
DOI: 10.1159/000086880
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Ready-to-Eat Cereals in Relation to Health and Diet Indicators among School Adolescents in Crete, Greece

Abstract: Background/Aims: We aimed at examining the intake of ready-to-eat cereals (RTEC) among adolescents in Crete, Greece, and investigate relationships with health and diet indicators. Methods: A sample of 392 adolescents (183 boys, 209 girls) aged 15 ± 0.4 years, attending high schools of two major counties in Crete, was studied to determine consumption of RTEC using a frequency questionnaire. Anthropometric measurements were performed and blood was drawn for analysis of serum lipoproteins and blood glucose (BG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
37
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 59 publications
7
37
2
5
Order By: Relevance
“…Another beneficial effect of RTEC consumption is that the majority of the adolescents consume them with milk (13,14,18) , which is in accordance with the results of the VYRONAS study where it was shown that milk and cereals were the main foods consumed at breakfast in both genders.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Another beneficial effect of RTEC consumption is that the majority of the adolescents consume them with milk (13,14,18) , which is in accordance with the results of the VYRONAS study where it was shown that milk and cereals were the main foods consumed at breakfast in both genders.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the findings of the present work are not in accordance with the results reported by van den Boom et al (18) , where 49?8 % of the studied population (aged 2 to 24 years) reported eating RTEC. Regarding the frequency of consumption of RTEC, in the VYRONAS study 18 % of the school adolescents ate RTEC at least once per week, which is not in accordance with the findings reported by Kafatos et al (13) where 43 % of adolescents ate RTEC at least once per week. Finally, we demonstrated that RTEC consumption decreased significantly as girls became older, which is in accordance with the findings of National Heart, Lung, and Blood Institute Growth and Health Study (19) in girls.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Concerning ready-to-eat cereal intake, our results are in accordance with evidence suggesting that ready-to-eat cereal consumption protects against childhood obesity. Kafatos et al (11) found that adolescents who are daily consumers of ready-to-eat cereals had lower mean BMI, WC and WHtR values, compared with non-consumers and occasional consumers. Other cross-sectional (50)(51)(52) and prospective studies (53,54) have shown similar results.…”
Section: Discussionmentioning
confidence: 99%
“…soda, juice and soft drinks) are associated with enhanced risk of children and adolescents being overweight or obese (8,9) . On the other hand, some studies have identified food groups whose intake has an inverse association with obesity, such as fruits, vegetables, ready-to-eat cereals and dairy products (10)(11)(12) . However, the results regarding the role of specified food groups in the development of overweight/ obesity remain controversial in paediatric populations.…”
mentioning
confidence: 99%